Computational studies on elastomeric diaphragm of membrane pump performance using purely lagrangian and coupled eulerian-lagrangian methods / Mohd Norshahid Mohd Idris - Mohd Norshahid , Mohd Idris (2018)
This research project was conducted to explore the capabilities of Abaqus fluid-structural analysis using Coupled Eulerian-Lagrangian (CEL) elements in simulating fluid induced deformation on a diaphragm of commercially available air operated double diaphragm pump. Result of the CEL analyses are compared with fully Lagrangian element which in this study was run in dynamic explicit using Abaqus/Explicit solver for sake of consistency. Previous numerical studies of quasi-static analyses (Implicit) were found not able to simulate the fluid induced deformation on the diaphragm. An FKM based elastomer from Freudenberg-NOK Sealing Technologies which typically used in diaphragm application and material properties of water was chosen in this study. The CEL analyses were found to be able to simulate the deformation that was cause by the fluid flow. However, significant effort in terms of pre-processing (defeaturing the models) and trouble-shooting are required to obtain convergence on the CEL analysis. On the other hand, the fully Lagrangian analysis was easy to setup and very stable in terms of convergence. Without correlation study with the actual part, it is not known whether the FE simulation result is accurate. However, these results and observations are useful in determining the capabilities of the CEL method by Abaqus.